THE CONCEPT OF WIND AND DUST IN THE QUR’ĀN; A Study of Surah Ibrahim (14):18 - Nur, Afrizal; Syafieh, Syafieh; Kholiska, Raden Kurnia (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2021)
The article explains of one verses from the verse of amtal, namely Ibrahim verse 18 which discusses the interpretation of the tafsir scholars who explain the action committed by infidels and the ashes that are dust by strong winds when the wind blowns. The related example is the dust which blown by the wind because the dust turns out to be nothing and you will not be able to do anything if you are faced with strong winds in the high wind season, surely the dust will fly everywhere chaotically and will not be able to return to original place. Besides that, the dust that is contained in the Qur’ān is flying dust, where the flying dust has a negative impact and unbenefit to human health and the environment. This fact provides a very broad discourse enrichment, that the wind can occur if one day there is air pressure in the horizontal direction, there will be a movement of air mass transfer from a place with high air pressure to a place with low air pressure. Dust particles are known as small numbers of particles that are lifted up by the force of wind stress. The value of the wind stress force in this event is expressed by the fluid or threshold. This threshold depends not only on the properties of the fluid, but also on the gravity and cohesive forces between the particles which oppose the lift force of the fluid